Analisis Kinerja Lalu Lintas Pada Simpang Empat Bersinyal Di Kawasan Jalan Nusa Indah Dan Jalan PB. Sudirman - noufal cahyanto (Journal of Science and Engineering, 2025)
This study aims to analyze traffic performance at signalized intersections in the Nusa Indah and PB Sudirman areas. The study was conducted to evaluate the level of service (Level of Service/LOS), intersection capacity, degree of saturation, traffic delays, and queue lengths at each intersection arm. The analysis method refers to the Indonesian Road Capacity Manual (MKJI) guidelines, using data on traffic volume, signal timing, intersection geometry, and surrounding environmental conditions. The analysis results indicate that variations in flow during peak hours have a significant impact on increasing delays and degree of saturation, so that intersection performance tends to decline at certain times. Based on the evaluation, it is necessary to optimize signal timing, rearrange the intersection arm configuration, and potentially add a special phase for turning vehicles to improve traffic flow. This study is expected to be a basis for traffic engineering planning to improve intersection performance in the area.